Progress as a discourse of progress - Schmid-Zartner, Rainer; Hobl, Robert (Momentum Quarterly, 2014)
Social progress in democratic societies is contingent on the possibility of all members of that society to participate in its discourses on progress. Hence, we define (social) progress as societies’ capacities to reflect upon it, and decide and act upon these reflexions on both the individual and societal level. This means, societies need to enable all their members to do this in a meaningful way, and this enabling centrally takes place in the education system, specifically in classroom teaching. Teaching that fulfils this democratic task needs to go beyond the notion of competencies that current debates on education focus upon. The cultivation of reflexive capabilities is an essential complement of competency-oriented learning and teaching. This paper describes teaching and learning practices that go beyond the uses of knowledge in an instrumental sense and provoke reflections upon its relevance in order to negotiate the meaning of what is being taught. We illustrate this with examples and experiences from the teaching of mathematics. This is hardly an obvious subject for reflexive methodologies but it is all the more essential as reflexive mathematics teaching enables pupils to explore the prerequisites and limitations of formal rationality themselves.
Keywords: progress; reflexion; education; classroom teaching; Mathematics